Transcatheter device closure of ruptured sinus of Valsalva: Immediate results and short term follow up - Sen Supratim; Chattopadhyay Amitabha; Ray Mily; Bandyopadhyay Biswajit (Wolters Kluwer Medknow Publications, 2009)
This is a retrospective, observational study comprising of eight patients with isolated rupture of the sinus of Valsalva (RSOV) who underwent transcatheter device closure. The mean age of presentation was 32.8 ± 10.0 years. New York Heart Association (NYHA) class at the time of presentation was II (six patients) and III (two patients). The RSOVs were all closed using a patent ductus arteriosus device. The mean procedural time was 42.3 ± 5.4 minutes, while the fluoroscopic time was 24.5 ± 6.9 minutes. All had complete closure of the shunt. The average hospital stay was 2.9 ± 1.1 days. There were no major complications. The patients were followed up for a mean of 11.3 ± 4.1 months. At the time of the last follow up all the patients were in NYHA class I. We conclude that in the short term, transcatheter closure of isolated RSOV is a viable alternative to surgical repair.